Dampak Sertifikasi Terhadap Lembaga Pendidikan Islam - Raikhan Raikhan (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
The purpose of this study was to determine: (1) the impact of the certification program on the pedagogic competence of teachers, (2) the impact of the certification program on the professional competence of teachers, (3) the impact of the certification program on teacher personality competencies, and (4) the impact of the certification program on teachers' social competence. This study uses a type of qualitative research, while data collection procedures are carried out through observation, interviews, and documentation. The results of the study indicate that: (1) The certification program does not have a good enough impact in improving the pedagogic competence of teachers, teachers still cannot operate IT while doing learning, teachers are indifferent in developing the curriculum, but in conducting assessments for the sake of learning the certification program already have a pretty good impact. (2) In improving the professional competence of the certification program has not had a good impact, because when doing learning the teacher tends to use the lecture method only. (3) The certification program has a good impact in improving the individual competency of teachers related to providing examples for their students and in increasing the activity of teaching, but certification teachers cannot provide examples related to discipline following the morning apples. (4) Certification programs have a fairly good impact on improving teacher social competence, the ability of teachers to work with colleagues is well established, certification programs also have a good impact on the ability of teachers to communicate with school residents, but certification programs are still not have a good impact with regard to the teacher's ability to communicate with students